Implementasi Hypnoteaching Dalam Pembelajaran pada Guru-guru Matematika di Kabupaten Takalar - Jafaruddin; Ilham Minggi; Sulaiman (Jurnal Hasil-Hasil Pengabdian dan Pemberdayaan Masyarakat, 2023)
This Community Service Program aims to improve the professionalism of educators and education personnel through the application of Hypnoteaching. The main focus is to make learning more engaging and effective by ensuring teachers are able to identify, explain and implement Hypnoteaching models according to the subjects taught. The training process involves key steps, from introducing the concept of Hypnoteaching to providing guided exercises to put it into practice.The results of the training showed significant changes in the participating teachers. They experienced improved understanding and skills in applying Hypnoteaching, creating a supportive and relaxed learning environment. Periodic evaluations showed consistent improvement, supported by teachers' high internal motivation. This PKM program makes a positive contribution to mathematics learning by empowering teachers through this innovative approach, creating a positive impact on students' learning experience